Replace x with the binomial a - 2.
f(a - 2) = [3(a - 2) + 5]/(a- 2)
f(a - 2) = [3a - 6 + 5]/(a - 2)
f(a - 2) = [3a - 1]/(a - 2)
f(a - 2) = (3a - 1)/(a - 2)
Done.
answer ...
to halp you and thank you
Hello,
What we want to do is multiply 1/6 by each value within the parentheses individually.
So, it would be:
(1/6) * (18x) = 3x
(1/6) * (-24) = -4
Together, this would be 3x-4.
Hope this helps!
Answer:
I think it is C but can't be sure because B isn't clear.
Step-by-step explanation:
D the formula is v=(pie)(r)2(h)
Sorry I don’t have the right tools to do the equation right. But it’s D